GE_GERICHTE P/10864/2024 vom 16. April 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;LÉSION CORPORELLE SIMPLE;AGRESSION;BRIGANDAGE;VOL(DROIT PÉNAL) | CPP.310; CP.123.al1; CP.134; CP.139; CP.140